PERLINDUNGAN HUKUM DATA PRIBADI SEBAGAI HAK PRIVASI - Kusnadi, Sekaring Ayumeida (AL WASATH Jurnal Ilmu Hukum, 2021)
Everyone must have personal data. Personal data is something that is inherent in everyone. Personal data is something that is sensitive. Personal data is something that must be protected because it is the right of everyone's privacy. The right to privacy is a constitutional right of citizens which has been regulated in the 1945 Constitution of the Republic of Indonesia. A constitutional right is the obligation of a state towards its citizens. In Indonesia, there are currently many legal problems that misuse someone's personal data for personal gain. However, currently the handling of these legal issues has not been maximized due to the absence of norms in the legal protection of personal data. The purpose and focus of this research is to find out the essence of legal protection of personal data as a right of privacy and a form of legal protection of personal data as a right of privacy in Indonesia. The research method used in this research is normative juridical, through a conceptual approach. The result of this research is that the essence of legal protection of personal data as privacy rights is a constitutional right of citizens. Indonesia does not yet have laws and regulations that form the legal basis for the protection of personal data. Therefore, in the legal protection of personal data, Indonesia experiences a vacuum of norms so that it cannot optimally protect the personal data of citizens.